2016
DOI: 10.1002/eap.1450
|View full text |Cite|
|
Sign up to set email alerts
|

Re‐evaluation of individual diameter : height allometric models to improve biomass estimation of tropical trees

Abstract: Abstract. Accurate estimation of tree biomass is necessary to provide realistic values of the carbon stored in the terrestrial biosphere. A recognized source of errors in tree aboveground biomass (AGB) estimation is introduced when individual tree height values (H) are not directly measured but estimated from diameter at breast height (DBH) using allometric equations. In this paper, we evaluate the performance of 12 alternative DBH : H equations and compare their effects on AGB estimation for three tropical fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
41
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 22 publications
3
41
0
Order By: Relevance
“…The Weibull model, also commonly preferred for lowland rainforests (e.g. [17]) and in montane forests in Peru [26] was not the preferred in our study area neither. Our results do not support the notion that a truly asymptotic model, more realistic biologically, is preferred over other types of height-diameter allometric models [23,31].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…The Weibull model, also commonly preferred for lowland rainforests (e.g. [17]) and in montane forests in Peru [26] was not the preferred in our study area neither. Our results do not support the notion that a truly asymptotic model, more realistic biologically, is preferred over other types of height-diameter allometric models [23,31].…”
Section: Discussionmentioning
confidence: 90%
“…Several authors have shown the significant biases in AGB estimates associated with using regional height-diameter models [19,2326] and have highlighted the need for local site-specific models. Our results show that using a local height-diameter allometric model for AGB estimates significantly reduces overestimation of AGB compared with Feldpausch et al [17] model for East or Central Africa (up to 78 and 105% overestimates respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uncertainties may come from the images used and measurement errors of field observations for the tree variables involved in allometric equations, including tree height and diameter at breast height (DBH) [4,[90][91][92]. In the present work, five remote sensing variables were selected and they were all significantly correlated with the sample plot AGB at the significance level of 0.01.…”
Section: Uncertainty Analysis Of Forest Biomassmentioning
confidence: 99%